2021
DOI: 10.3389/fcimb.2021.769922
|View full text |Cite
|
Sign up to set email alerts
|

E-NTPDases: Possible Roles on Host-Parasite Interactions and Therapeutic Opportunities

Abstract: Belonging to the GDA1/CD39 protein superfamily, nucleoside triphosphate diphosphohydrolases (NTPDases) catalyze the hydrolysis of ATP and ADP to the monophosphate form (AMP) and inorganic phosphate (Pi). Several NTPDase isoforms have been described in different cells, from pathogenic organisms to animals and plants. Biochemical characterization of nucleotidases/NTPDases has revealed the existence of isoforms with different specificities regarding divalent cations (such as calcium and magnesium) and substrates.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 140 publications
(206 reference statements)
0
5
0
Order By: Relevance
“…During infectious processes, the presence of serum ATP as a result of tissue injury or lysis of infected cells, signals the formation and intensity of the immune response [ 48 ]. T. cruzi has a TcNTPDase on its surface that is capable of hydrolyzing ATP into ADP and the latter into AMP, preventing or hindering the formation of an effective immune response [ 33 ]. A recent study, by our group, demonstrated that the culture of VERO cells infected with a hemi-knockout clone of T. cruzi for the TcNTPDase-1 gene (KO +/−) was able to decrease not only adhesion, but also the infection of these cells in this in vitro model [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…During infectious processes, the presence of serum ATP as a result of tissue injury or lysis of infected cells, signals the formation and intensity of the immune response [ 48 ]. T. cruzi has a TcNTPDase on its surface that is capable of hydrolyzing ATP into ADP and the latter into AMP, preventing or hindering the formation of an effective immune response [ 33 ]. A recent study, by our group, demonstrated that the culture of VERO cells infected with a hemi-knockout clone of T. cruzi for the TcNTPDase-1 gene (KO +/−) was able to decrease not only adhesion, but also the infection of these cells in this in vitro model [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…NTPDases have been described as being associated with several cellular functions, such as differentiation, multiplication, division, and apoptosis [ 33 ]. Present in various cell types and tissues, analogs of these enzymes are also found in the membranes of protozoan microorganisms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations